An Automated Methodology for Assessing Anatomy-Specific Instrument Motion during Endoscopic Endonasal Skull Base Surgery - Harbison, R. Alex; Li, Yangming; Berens, Angelique M.; Bly, Randall A.; Hannaford, Blake; Moe, Kris S. (Journal of Neurological Surgery Part B: Skull Base, 2017)
Objectives Describe instrument motion during live endoscopic skull base surgery (ESBS) and evaluate kinematics within anatomic regions.Design Case series.Setting Tertiary academic center.Participants A single skull base surgeon performed six anterior skull base approaches to the pituitary.Main Outcomes and Measures Time-stamped instrument coordinates were recorded using an optical tracking system. Kinematics (i.e., mean cumulative instrument travel, velocity, acceleration, and angular velocity) was calculated by anatomic region including nasal vestibule, anterior and posterior ethmoid, sphenoid, and lateral opticocarotid recess (lOCR) regions.Results We observed mean (standard deviation, SD) velocities of 6.14 cm/s (1.55) in the nasal vestibule versus 1.65 cm/s (0.34) near the lOCR. Mean (SD) acceleration was 7,480 cm/s2 (5790) in the vestibule versus 928 cm/s2 (662) near the lOCR. Mean (SD) angular velocity was 17.2 degrees/s (8.31) in the vestibule and 5.37 degrees/s (1.09) near the lOCR. We observed a decreasing trend in the geometric mean velocity, acceleration, and angular velocity when approaching the pituitary (p < 0.001).Conclusion Using a novel method for analyzing instrument motion during live ESBS, we observed a decreasing trend in kinematics with proximity to the pituitary. Additional characterization of surgical instrument motion is paramount for optimizing patient safety and training.
Keywords: surgical instrument motion; surgical kinematics; endoscopic skull base surgery; surgical safety; surgical training